Seasonal Turnover and Functional Structure of the Foliar Mycobiota in a Gondwanan Temperate Forest Keystone Tree - Molina, Lucia (2025)
Fungal communities inhabiting leaves are key players in ecosystem processes but remain largely unexplored in Southern Hemisphere temperate forests. We characterized the foliar mycobiota of Nothofagus pumilio, a dominant deciduous tree in Patagonian forests, using ITS1 metabarcoding across seasons and tree health conditions. We detected 426 fungal taxa, including a 40-Amplicon Sequence Variant (ASV) core mycobiome persisting year-round. Fungal richness and biomass increased significantly in autumn, coinciding with leaf senescence, and community composition shifted markedly between seasons. Spring leaves were enriched in pathogens and basidiomycetous yeasts, while autumn leaves hosted more saprotrophs, ascomycetous yeasts, and lichen-associated fungi. Tree health had limited influence on overall community structure, but symptomatic trees showed higher ASV richness and specific indicator taxa, including the pathogen Trichosporiella multisporum and members of the Taphrinaceae and Saccotheciaceae families. Despite taxonomic turnover, ecological guilds remained relatively stable, suggesting functional redundancy. These findings reveal a seasonal successional trajectory in the foliar mycobiota of N. pumilio, from early-colonizing endophytes in spring to diverse decomposer assemblages in autumn. This study provides the first high-throughput insight into the structure and dynamics of foliar fungal communities in Southern Hemisphere temperate forests, offering a baseline for understanding microbial roles in forest health and resilience.